Picasso and the mysteries of life La Vie - Robinson, William H. 1955- (Cleveland masterwork series, 2012)
"Few artistic moments are as instantly recognizeable as Pablo Picasso's Blue Period, and from it La Vie (Life) has emerged as the culminating masterpiece. This book not only examines La Vie's history and physical structure in unprecedented detail but also uses the painting as the touchstone for exploring a broad array of issues vital to modernist culture of the 19th and 20th centuries. New contextual analysis is provided for understanding the painting's enigmatic subject, along with its relationship to the art of Picasso's contemporaries. The author explores unexpected connections to both earlier and later works by Picasso, to Spanish and French literature, and perhaps most surprisingly, to sources in popular culture. Picasso's depiction of his close friend Carles Casagemas, a key figure in the painting, provides the impetus for investigating suicide and the concept of the artist as Christ-martyr as foundational themes in modern art and literature. Auguste Rodin and Paul Gauguin's influence on the young Picasso also emerge with new insight and clarity" --Inside cover.